The Choice of Suffix Variants for Participial Adjective in Corpus of Malaysian e-Newspapers. - Chai Jian Mei; Ong Sook Beng, Christina (Pertanika Journal of Social Sciences & Humanities, 2018)
In view of the dubiety caused by the concurrent use of suffix -t and -ed among Malaysians in forming the participial adjective, local newspaper texts were analysed in order to identify the preferred suffix variant used by Malaysian writers. Using corpus-based methodology, 12 predetermined words that can take suffix -t and -ed were generated from the selected e-newspaper prior to analysing them using WordSmith Tools 5 (WST5). The 12 words that belong to the adjective word class were categorised in accordance with the word form (-t and -ed) before comparison between both suffix variants was made. Findings revealed that while both suffix -t and -ed were used by Malaysians, the overall figure for the -t form is higher, thus indicating that Malaysians generally prefer to use the suffix -t to form the participial adjective. Nevertheless, the insertion of suffix -ed and -t to irregular verbs as a means to reflect adjectival function could possibly be deemed as a form of linguistic explicitness exhibited by a local variety. Because language is constantly evolving, pedagogically, educators should consider adopting the descriptive grammar and be flexible in accepting the use of both suffixes.